2020
DOI: 10.1155/2020/1631869
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Linguistic Z-Number QUALIFLEX Method and Its Application to Large Group Emergency Decision Making

Abstract: After an unconventional emergency event occurs, a reasonable and effective emergency decision should be made within a short time period. In the emergency decision making process, decision makers’ opinions are often uncertain and imprecise, and determining the optimal solution to respond to an emergency event is a complex group decision making problem. In this study, a novel large group emergency decision making method, called the linguistic Z-QUALIFLEX method, is developed by extending the QUALIFLEX method usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 44 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…How to deal with uncertain information effectively is an open problem. Several mathematical theories have been discussed for solving this problem, such as Bayesian theory [2], fuzzy set theory [3,4], Dempster-Shafer (D-S) evidence [5,6], possibility theory [7,8], D-numbers [9,10], Z-numbers [11,12], rough set theory [13,14], and fractal theory [15,16]. Especially D-S evidence theory, as a rational and effective method for dealing with uncertain information, has the following three advantages.…”
Section: Introductionmentioning
confidence: 99%
“…How to deal with uncertain information effectively is an open problem. Several mathematical theories have been discussed for solving this problem, such as Bayesian theory [2], fuzzy set theory [3,4], Dempster-Shafer (D-S) evidence [5,6], possibility theory [7,8], D-numbers [9,10], Z-numbers [11,12], rough set theory [13,14], and fractal theory [15,16]. Especially D-S evidence theory, as a rational and effective method for dealing with uncertain information, has the following three advantages.…”
Section: Introductionmentioning
confidence: 99%
“…The probabilistic linguistic weighted averaging operator combining Dempster–Shafer evidence theory was advanced by Li and Wei [ 22 ] for the EDM of a serious mine accident. Ding et al [ 11 ] suggested a large group EDM method by extending the QUALIFLEX method using linguistic Z-numbers. Ashraf and Abdullah [ 2 ] designed three EDM algorithms using TOPSIS, grey relational analysis and Einstein aggregation operators under a spherical fuzzy environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Different approaches have been adopted to rank the EDM solutions, such as Technique in Order of Preference by Similarity to Ideal Solution (TOPSIS) [ 2 ], VIseKriterijumska Optimizacija I Kompromisno Resenje (VIKOR) [ 60 ], Weighted Distance Based Approximation (WDBA) and COmbinative Distance-based ASsessment (CODAS) [ 46 ], DEcision-MAking Trial and Evaluation Laboratory (DEMATEL) [ 4 ], QUALItative FLEXible multiple criteria (QUALIFLEX) [ 11 ] and Preference Ranking Organization METHod for Enrichment Evaluations II (PROMETHEE II) [ 45 ]. Although these methods are beneficial to EDM, they assume that DMs are completely rational.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, it has obtained a lot of attentions. Some researchers presented theoretical studies of Z-numbers, like Z*-numbers [9], arithmetic operations of discrete and continuous Z-numbers [10,11], modeling of Z-number [12], approximate reasoning of Z-numbers [13], functions based on a Z-number set [14], total utility of Z-numbers [15] and so on; while other researchers developed some applications of Z-numbers, such as Z-evaluations [16], sensor data fusion using Z-numbers [17], decision making approaches with Z-numbers [18][19][20][21][22][23][24], Z-numbers-based stable strategies analysis in evolutionary game [25], Z-numbers-based medicine selection of the patients with mild symptoms of the COVID-19 [26], Z-numbers-based environmental assessment under uncertainty [27] and so on.…”
Section: Introductionmentioning
confidence: 99%